A lost Chinese inscribed stone, some Old Hungarian script, two notable copies of Angelo Rocca's Bibliotheca Apostolica Vaticana (1591), and an addition to John Donne's library. Issue 2 (4th March 2021) - Poole, William
ABSTRACT: This article discusses a lost Chinese inscribed stone known to have been in Oxfordshire in the late seventeenth century. It then proceeds to identify a hitherto unnoticed book in Oxford belonging to the poet John Donne, featuring extensive manuscript and printed inserts. Another copy of the same text, Angelo Rocca's Bibliotheca Apostolica Vaticana (1591), also in Oxford, is then revealed to contain a manuscript account of Hungarian "runes".